Ethical Issues in Political News Coverage: A Case Study of 2015 General Elections in Turkey - Bekcan, Can (Eastern Mediterranean University EMU, 2017)
Journalism ethics is important to study, and this study focuses on infringements of journalism ethics during the General Elections of 2015 in Turkey. Its aim to find out five most circulated newspapers’ which are Zaman Hürriyet, Posta, Sözcü and Sabah, infringement of journalism ethics between two General Election of June 7th and November 1st in 2015. In this study, content analysis was used without physical measurement. Only cover pages were analysed which news was relevant to political issues. A coding sheet was used to analyse, and its reliability was .97 according to Cohen’s formula. The study was conducted to answer two major questions. (1) Is there any unethical news has been published during the two elections, and (2) what changed between the two elections on cover pages news according to journalism ethics? At the end of the research, infringements of journalism ethics were remarked by all newspapers during the elections. Main conspicuous thing is that newspapers infringed journalism ethics according to being pro-government or not. Especially, most infringements have happened before the elections, and newspapers were being changed their attitudes according to election results. Keywords: journalism ethics, general election, Turkey, content analysis

ÖZ: Gazetecilik etiği önemli bir konudur ve bu çalışma Türkiye’deki 2015 Genel Seçimleri sırasında yapılmış etik ihlallere odaklanmıştır. Bu çalışma, en yüksek tirajlı beş gazete olan; Zaman, Hürriyet, Posta, Sözcü ve Sabah’ın, 7 Haziran ve 1 Kasım 2015’te gerçekleşen Genel Seçimler’deki gazetecilik etiği ihlallerini araştırmıştır. Çalışmada, içerik analizi kullanılmış ve fiziksel ölçüm hesaba katılmamıştır. Sadece ön sayfalardaki, politikayla ilgili haberler analiz edilmiş, analiz için kodlama tablosu hazırlanmış ve Cohen’in formülüne göre .97 ile kodlama tablosunun uygulanabilirliği kanıtlanmıştır. Çalışma, iki soruya cevap bulmak için yapılmıştır. Gazetecilik etiğine göre, ön sayfada yayınlanan haberlerde; (1) iki seçim süresince etik dışı haberler yayınlanmış mıdır? (2) iki seçim arasında ne gibi bir değişiklik vardır? Araştırmanın sonucuna göre, bütün gazeteler seçimler süresince etik ihlaller yapmıştır. Asıl belirgin olan olgu da gazetelerin etik dışı haberler yapmaları yayın politikalarıyla olduğuydu. Özellikle, etik ihlallerin çoğu seçimlerden önce yapılıyor ve seçim sonucuna göre gazetelerin tutum belirlediği göze çarpıyor. Anahtar Kelimeler: gazetecilik etiği, genel seçimler, Turkey, içerik analizi
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2017. Supervisor: Assoc. Prof. Dr. Metin Ersoy.
Keywords: Communication and Media Studies; Journalism-Political News-Social aspects-Turkey; journalism ethics; general election; Turkey; content analysis